Generic applicability of non-destructive biomass yield models for willow short rotation coppice: A case study for Germany and Lithuania. (February 2019) - Linkevičius, Edgaras; Schröder, Jens; Röhle, Heinz
Abstract: Rapid development and cultivation of willow Short Rotation Coppice (SRC), driven by international companies, demand reliable, easily applicable and cheap, non-destructive biomass yield estimation methods that are not yet available in Lithuania. During the last years, knowledge transfer between research institutions and industry across Europe has therefore been an important and fostered topic in this area. This study focuses on non-destructive biomass estimation methods, developed by German research institutions, and evaluates them under Lithuanian growth conditions. The common allometric power equation (APE), quadratic mean diameter (QMD), and yield appraisal (YA) approaches were tested for estimation bias, precision and accuracy. In total, data from 39 commercial willow SRC were used for the analyses. According to the results, mean annual oven dried biomass increment was higher in German willow SRC compared to Lithuanian willow SRC. However, there were no statistically significant differences between the scaling coefficients of plot specific allometric power equations. The developed country-specific common APE were characterize by very high coefficients of determination (R2 >0.96). Predictions of both common models were in line with predictions of plot-specific models and none of these models produced a higher bias or a significantly lower precision compared to plot-specific APE models. Compared with the other applied methods (QMD and YA), common APEs produced the most accurate estimations for Lithuanian and German willow SRC. Based on our findings we conclude that the transfer of non-destructive biomass estimation methods between Lithuania and Germany is scientifically sound and offers an important synergetic potential for local industries. Highlights: Higher yields of willows do not lead to different shapes of allometric equations. Common allometric equations produce results, comparable with plot specific equations. Transfer of non-destructive biomass estimation methods between countries is possible.